An Analysis of Speech Acts in Ernest Hemingway’s The Killers - Masruroh Masruroh; Sulistyaningsih Sulistyaningsih; Lailatul Musyarofah (International Journal of English and Applied Linguistics (IJEAL), 2023)
The article begins by highlighting the importance of language as a means of communication and the significance of studying the relationship between language and context. It also discusses the relevance of analyzing speech acts in understanding the intended meaning behind utterances. Previous studies on speech acts in Hemingway's works are mentioned, focusing on locution, illocution, and perlocution, or the form and meaning of speech acts. The research methodology employed in this study is descriptive-qualitative, involving the analysis of dialogue fragments from the short story. The data collection technique involves extracting relevant conversations from the story and categorizing them based on the speaker, hearer, topic, and setting. The analysis includes identifying the types of speech acts used, exploring their possible meanings, classifying them into five general functions (assertives, commissives, directives, expressives, and declaratives), and categorizing them based on sentence structure (declarative, interrogative, imperative, or exclamative). The findings and discussions section presents several examples of speech acts found in the short story, describing the locution, illocution, perlocution, and classifications of each speech act. The results demonstrate the diverse range of speech acts employed by the characters in "The Killers" and their impact on communication within the narrative.